Comparative study of control strategies for a grid connected two-stage single-phase inverter with battery integration - Yamaguti, Nelson Nayoshi Nakamoto (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2024.